The silent sisters - Dugoni, Robert (Seattle : Thomas & Mercer, 2022)
An American sleeper cell in Russia goes silent--and it's one man's duty to find them.
Keywords: Intelligence officers -- Fiction; Moles (Spies) -- Fiction; Undercover operations -- Fiction; United States -- Central Intelligence Agency -- Officials and employees -- Fiction; Moscow (Russia) -- Fiction; Spy fiction